Sistema de reclutamiento y selección de personal para la empresa Multisa CAD. - Núñez Aldaz, Pablo José (2023)
The purpose of the present work titled Personnel Recruitment and Selection System for the Multisa CAD Company, seeks mainly to propose a personnel recruitment and selection system for the Multisa CAD Company. The methodology applied was based on a mixed approach of descriptive type, with a deductive method, the main findings showed that there are difficulties with the time in which the sub process of recruitment is delayed, also in many processes it is not achieved the recruitment due to lack of suitable profiles for vacancies, so the structuring of the recruitment and selection system for the company Multisa CAD and the implementation of 9 strategies for recruitment and 9 strategies for the selection of personnel arises.